In vitro expression of native H5 and N1 genes of avian influenza virus by using Green Fluorescent Protein as reporter - Hartawan, Risza; Robinson, K.; Mahony, T.; Meer, J. (Indonesian Animal Sciences Society, 2011)
The hemagglutinin and neuraminidase are important immunogen of avian influenza virus that are suitable for recombinant experimentation. However, both genes have been experienced rapid mutation resulting in diverse variety of genotypes. Hence, gene expression in recombinant systems will be difficult to predict. The objective of the study was to examine expression level of H5 and N1 genes from a field isolate by cloning the genes into expression vector pEGFP-C1. Two clones respresenting fulllength of H5 and N1 gene in plasmid pEGFP-C1 were transfected into chicken embryo fibroblasts (CEF), rabbit kidney (RK13) and African green monkey kidney (VERO) cells using Lipofectamine âPlusâ reagent. The experiment showed level of gene expression in the VERO cell was higher than in the RK13 and CEF cells. Observations using fluorescent microscopy and Western blotting revealed that the N1 gene was expressed better in all cells compared to the H5 gene. Key Words: H5N1 Virus, Hemagglutinin, Neuraminidase, Gene Expression, Green Fluorescent Protein